Simulation test on water and salt transport characteristics of saline soil in Uzbekistan under large temperature difference - Fang Zheng; Wenqiang Li; Zhanping Song; Dongdong Xu; Junbao Wang; Yan Wang; Yuwei Zhang (PLoS ONE, 2025)
To investigate the characteristics of water and salt migration (WSM) in saline soils subjected to climate conditions characterized by large temperature differences. In this paper, salted soil highway roadbeds in Uzbekistan were selected as the background for the study, and the salted soils in the region of the site were remodeled through a field study and based on field data. Subsequently, utilizing the assembled laboratory test apparatus, a model test of the WSM on the remodeled saline soil was carried out to analyze the behavior of the WSM in response to large temperature differences, the resulting soil deformation, and the influence of varying cold-end temperatures and alternating cooling and heating times on the WSM. The findings indicated that the temperature profile with in the soil column (SC) exhibits a “wavy” pattern as a result of thermal conductivity. During the freezing phase, water migrates from the lower section to the upper section in response to the temperature gradient and soil-water potential. Conversely, during the melting phase, water diffuses and migrates from the upper section downward in the form of steam molecules due to the action of evaporation. This process culminates in a “C” shape distribution of the curve of the water content inside the SC. During the freezing process, salt migrates from the bottom to the top along with the liquid water. Conversely, during the melting process, salt accumulates at the top of the SC accumulates. This phenomenon results in an “S” distribution of the salt content inside the SC. At the end of the freeze-thaw cycle (FTC), the deformation of the saline soil increased with the decrease of the cold end temperature, and the alternating time between heat and cold did not produce significant changes in the deformation of the saline soil. The moisture content at the upper end of the SC increases with decreasing cold-end temperature. The increase in the number of FTCs exacerbates the salinization of the soil in a certain part of the interior of the SC. The findings of this research may offer a theoretical foundation and technical assistance for the design of subgrade structures in saline soils subjected to climates characterized by large temperature differences.